Identificação organizacional cooperativa: a influência de um novo construto sobre o clima organizacional - Bento, Marcia Helena dos Santos (2019)
An identity is formed by characteristics that differentiate one person from another or one organization from many other organizations. Cooperatives have several characteristics that differentiate them from conventional societies. The Action Plan for a Cooperative Decade or Vision 2020, developed by the International Co-Operative Alliance, placed Identity as a central theme for the development and sustainability of cooperatives. In analyzing the influence of cooperative organizational identity from the perspective of organizational identification, on the organizational climate the following question is asked: How does Cooperative Organizational Identification influence the Organizational Climate of credit union employees? Thus the overall objective of this study was to analyze the influence of cooperative organizational identification on the organizational climate. To this end, an exploratory and descriptive empirical research was conducted, with mixed methods for the survey and analysis of the results. Initially, it developed, mainly from the Theory of Organizational Identity and the Declaration on Cooperative Identity, Values and Principles, a new construct called Cooperative Organizational Identity. From this construct, the Cooperative Organizational Identification scale was constructed, which, validated by experts, was submitted to a pilot test with 39 respondents. The Organizational Climate scale was translated and adapted cross-culturally, based on the equivalence pretest with almost 100% comprehensibility. These two scales comprised the questionnaire which, together with two more open-ended questions, were applied to 344 employees of three credit unions in Rio Grande do Sul. In these three cooperatives, semi-structured interviews were also conducted with people management managers in order to assess to ascertain their perception of cooperative identity, organizational identification, organizational climate, and how the influence of cooperative organizational identification has on the organizational climate. The analysis of quantitative data was performed with the support of SPSS and Amos software, and qualitative data with NVivo software. Exploratory and confirmatory factor analyzes were used at both scales, resulting in two second-order constructs with three first-order constructs each. Analysis of structural paths revealed that the first order construct 'Group Fit' is what most influences the Organizational Climate. The validated final model combined a second-order construct, 4 first-order constructs and 17 variables. The final results of the model demonstrated that the Organizational Climate is 83.7% explained by its Affective, Cognitive and Instrumental aspects. The analysis of qualitative data ratified the quantitative data by showing that 65.24% of employees believe that the Organizational Climate is positively influenced by the fact that they are a cooperative. By relating the managers 'responses to the employees' responses, it was noticed that they were aligned, mainly in identifying opportunities for improvement in the COI Group Fit Dimension, more specifically in Equality and Equity values.